Coach development as assemblage: mobilising assemblage thinking to examine coach learning within an endurance-running coach development intravention - Avner, Z.; Skebo, K.; Jones, L.; Denison, J.; Konoval, T.; Hall, E. T.; Radowits, R.; Downie, D. (Sports Coaching Review, 2024)
In this paper, we examine the learning of nine high-performance endurance running coaches over a seven-week poststructuralist-informed coach development workshop. Drawing on Deleuze and Guattari`s concept of assemblage as a novel analytical framework we explore the production of difference within the context of our learning assemblage, and why thinking and coaching differently remain challenging. Connecting content (e.g. coach learners, coach developers, learning materials and technologies, virtual and physical spaces) and expression (e.g. coaching norms and statements, privileged coach development knowledges and curricula) within a range of empirical materials generated throughout the workshops made visible multiple sociomaterial forces that reproduce coaching as a modernist formation, but also, more hopefully, possible lines of flight for coaches and coach developers (new ways of thinking and practicing) that have the potential to reconfigure endurance-running coaching in ways that are arguably more ethical and sustainable. We conclude by discussing the implications of these for the planning and doing of poststructuralist informed coach development work.